AGRONOMIC PERFORMANCE OF INTACTA RR2 SOYBEAN SUBMITTED TO DOSES OF GLYPHOSATE - Cesco, V. J. S. [UNESP]; Krenchinski, F. H. [UNESP]; Rodrigues, D. M. [UNESP]; Nardi, R.; Albrecht, A. J. P.; Albrecht, L. P. (Univ Federal Vicosa, 2018)
This study aimed at evaluating the agronomic performance of Intacta RR2 soybean submitted to the application of glyphosate doses in post-emergence. For this, two experiments were conducted in two locations (Palotina and Marechal Candido Rondon - Parana state). Applications were carried out with increasing rates of glyphosate (0, 720, 1,440, 2,160, 2,880, 3,600, 4,320 g a.e. ha(-1)), constituting seven treatments with an experimental design in randomized blocks with four replications, totaling 28 plots for each location. The cultivar used for both experiments was Monsoy 6210 Intacta RR2 IPRO (TM). The analyzed variables were phytotoxicity at 3, 7,14, 21 and 28 DAA, A-B and total chlorophyll index, final height, number of pods, 100-seed weight, and yield. A regression analysis was used. There was a positive behavior of the linear regression for phytotoxicity and a negative one for final height, number of pods, A-B and total chlorophyll index, and yield in the city of Palotina. In Marechal Candido Rondon, there were adjustments of the positive linear regressions for phytotoxicity, and negative linear regressions for chlorophyll index, final height, number of pods and yield. Results show that the glyphosate increase from the dose 1,440 g a.e. ha(-1) in the studied cultivar damaged the agronomic performance of the culture.
Keywords: Glycine max; yield; phytotoxicity; herbicides; transgenic soybean